DETERMINAN PEMANFAATAN PELAYANAN IMUNISASI POLIO DALAM MASA PANDEMI COVID-19 DI PUSKESMAS SRONDOL KOTA SEMARANG - Nisrina Aliftya; Septo Pawelas Arso; Wulan Kusumastuti (Jurnal Kesehatan Masyarakat (Undip), 2022)
Immunization is an effort to prevent infectious diseases that can go wrong with practice (PD3I). The strategic plan target (Renstra) from the Semarang City Health Office is used as a standard that must be achieved in an expertise program, which is 95%. In the sustainability of achieving the strategic plan target obtained from the results of the preliminary study, one of the health centers that has not yet reached the coverage of the polio program (OPV) is the Srondol Health Center, where a decrease in coverage was also found for two consecutive years, namely 2019 and 2020. This study aims to determine Factors that have a related with the use of polio during the Covid-19 pandemic at the Srondol Health Center, Semarang City. The type of research used is quantitative with a cross-sectional design. A total of 103 respondents were obtained through purposive sampling method. Data analysis was carried out univariate and bivariate using non-parametric statistical tests. The results showed that health care facilities (p = 0.044), health workers (p = 0.000), perceptions of vulnerability (p = 0.000), perceptions of seriousness (p = 0.008), perceptions of benefits (p = 0.000), and control to act ( p=0.004). are factors that have a relationship with the use of polio services during the Covid-19 pandemic at the Srondol Health Center, Semarang City.